AB0486 The Complete Response in Patients with Lupus Nephritis Treated with Mycophenolate Mofetil (MMF) as Their First Line Therapy. (10th June 2014) - Timlin, H.; Magder, L.; Petri, M.
Abstract : Background: The optimal therapeutic approach for lupus nephritis (LN) involves an induction phase to achieve remission followed by maintenance therapy to prevent relapses. Mycophenolate mofetil (MMF) has become the primary induction and maintenance therapy for lupus nephritis (LN). Objectives: The complete response rate is the most sensitive in detecting differences among therapeutic regimens. The purpose of this study was to assess complete response after starting mycophenolate mofetil (MMF) as initial therapy for class III, IV or V in immunosuppressant naïve patients with lupus nephritis by using 5 different criteria (BMS, ACR, LUNAR, ALMS, and ACCESS). Methods: 21 SLE patients began mycophenolate mofetil (MMF) shortly after a biopsy-confirmed diagnosis of lupus nephritis. They consisted of 18 females, 3 males, 9 African Americans, 8 Caucasians, and 4 other ethnicities. Ages ranged from 18 to 70 with a mean age of 37 (SD=15). There were 5 patients with class III, 9 with class IV, 4 with class III-V, 1 with class IV-V and 2 with class V lupus nephritis. The initial dose of mycophenolate mofetil (MMF) was 1000mg twice daily. If no improvement, it was increased to 1500 mg twice daily after one month. The baseline urine protein to creatinine ratio ranged between 0.635 to 11.91grams, with only 1 patient being below 1 gram at baseline. Patients were on a renal sparing regimen (52%) and hydroxychloroquine (86%). Depending on the response index, complete response was defined, as reaching a urine protein to creatinine ratio of <0.2-0.5 grams, improvement in creatinine or estimated glomerular filtration rate of 10-25%, normalization of urinalysis and tapering dose of steroids. The probability of complete response over time was estimated by using an approach that accommodated interval censored data. Results: The probability of response at 90 and 180 days is shown in Table 1 for each response index. Conclusions: This study demonstrates that patients with newly diagnosed lupus nephritis and previously naive immunosuppressant can reach complete response within 6 months after initiation of mycophenolate mofetil. Furthermore, the estimate of long term response was highest in the ACR criteria where reduction in urine protein creatinine ratio was below 0.20grams but no steroid taper was addressed. Our experience may show better results, because majority of the patients were prescribed hydroxychloroquine and because mycophenolate mofetil (MMF) was started at a therapeutic dose. The rate of complete response described here illustrate the considerable unmet need for more effective treatments. These data can be used to determine sample sizes for clinical trials in lupus nephritis; but also suggest that a more stringent complete response goal should be considered to help with predicting long term outcome. References: Wofsy D, Hillson JL, Diamond B. Arthritis Rheum 2012; 64:3660-5 Furie R, Arthritis Rheum 2011;63 Suppl Appel GB, Contreras G, Dooley MA, Ginzler EM, Isenberg D, Jayne D. J Am Soc Nephrol 2009 Rovin BH, Fur ie R, Latinis K, Looney RJ, Arthritis Rheum 2012;64:1215–26. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5878